2018
DOI: 10.1002/pd.5319
|View full text |Cite
|
Sign up to set email alerts
|

Interfering effect of maternal cell contamination on invasive prenatal molecular genetic testing

Abstract: In the case of Sanger sequencing, sensitivity to MCC was variable, while for MLPA, only high levels of MCC proved to be significant. Although the next-generation sequencing method was sensitive to low-level MCC, if MCC level is determined in parallel, accurate quantification of allelic ratios can help to interpret the diagnostic results. Knowledge of significant MCC levels allows correct prenatal diagnosis even if samples are not purely of fetal origin and repeated sampling can be avoided in many of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Prenatal samples are derived from the maternal body, and maternal cell contamination may greatly affect the accuracy of prenatal diagnosis 22 . Therefore, prenatal samples, including chorionic villus, amniotic fluid, and umbilical cord blood, are available for prenatal diagnosis after exclusion of maternal cell contamination 23 . In this study, STR analysis of the 700 prenatal samples showed no maternal cell contamination, and these prenatal samples were qualified for the subsequent analyses.…”
Section: Discussionmentioning
confidence: 91%
“…Prenatal samples are derived from the maternal body, and maternal cell contamination may greatly affect the accuracy of prenatal diagnosis 22 . Therefore, prenatal samples, including chorionic villus, amniotic fluid, and umbilical cord blood, are available for prenatal diagnosis after exclusion of maternal cell contamination 23 . In this study, STR analysis of the 700 prenatal samples showed no maternal cell contamination, and these prenatal samples were qualified for the subsequent analyses.…”
Section: Discussionmentioning
confidence: 91%